MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SEDERHANA MELALUI MODEL PICTURE AND PICTURE DI SEKOLAH DASAR - Wiwin Mintarsih; Acep Roni Hamdani (STKIP Subang, 2019)
This research is motivated by the low skill of writing essays for grade 3 students in elementary school. The low writing ability is due to writing learning in elementary schools often not being noticed. The selection of the right model will give students added value to the learning process so as to facilitate learning activities. One model that can be used by teachers in writing activities includes the picture and picture model, which is a learning model that uses series image media, namely images that are interrelated and form a whole story. The research method used is Classroom Action Research (CAR). The reason for using this method is to find out how to use the learning model in improving the results of learning activities at Nugraha Pelita Elementary School Jl. Field of Bunihayu Jalancagak Sports Subang Regency. The research subjects were class III Nugraha Pelita Elementary School Jl. Field of Bunihayu Jalancagak Sports Subang Regency. Based on the results of the study concluded as follows: 1) The process of learning activities by applying picture and picture to third grade students of SDN Nugraha Pelita, students are very enthusiastic and active in learning no longer feel bored or bored, this is indicated by an increase in essay writing skills to students; 2) Writing essay skills by applying the picture and picture model can increase, this can be proven by the results of the average value obtained by students which in each cycle has increased, starting from the initial data which only has an average value of 57, in the cycle I meeting 1 on average obtained by students is 65, and the first cycle of meeting 2 on average obtained by students is 70. Then in cycle II. meeting 1 the average value obtained by students is 74, and the second cycle of meeting 2 the average value obtained by students is 78. Then in the third cycle of meeting 1 the average value obtained by students is 81 and the second cycle of meetings 2 values averaged the average obtained by students is 85 which is included in criterion A (very good).